Philosophy and Laughter: Introductory Notes. Issue 4 (30th November 2020) - Olivier, Abraham
Abstract: Until recently, few philosophers worked on laughter, and it was typically viewed negatively. However, the last four decades have witnessed a significant increase in philosophical writings about and positive views of laughter. This introductory paper attempts to show that, in line with this development, contributions to this special issue explore various fresh theoretical, thematic, historical, and critical aspects of laughter and its relation to philosophy. These contributions can be divided roughly into two intersecting groups, with one group focused on the theoretical, thematic, and historical exploration of laughter, and the other on critical social and moral issues of laughter. They demonstrate how laughter matters to philosophers as a serious philosophical subject, and they take care to distinguish objectionable types of laughter from its constructive uses as social and moral critique and facilitator.